Retaining Talent in Digital, Technology and Innovation Department: Key Factors Influencing Retention at a GLC in Malaysia - Abdul Halim, Haney Shafira; Ab Latiff, Dilla Syadia (Information Management and Business Review, 2024)
Employee retention is crucial for organizational success, especially in dynamic fields like Digital, Technology, and Innovation. This correlational study investigated factors influencing employee retention within the DTI department of a Malaysian GLC, guided by Herzberg’s Two-Factor Theory. The study examined the relationship between employee retention (dependent variable) and compensation & benefits, work-life balance, career growth opportunities, and training & development (independent variables). Data was collected from a diverse sample of DTI employees using a comprehensive survey and analyzed using Statistical Package for Social Sciences (SPSS) version 29. The findings revealed no significant relationship between compensation & benefits, work-life balance, or career growth opportunities and employee retention. However, a significant positive relationship was found between training & development and employee retention. This study provides insights into the unique factors affecting retention in DTI departments and offers practical recommendations for creating a supportive work environment that enhances employee retention. Specifically, the study highlights the importance of robust training and development programs in fostering employee satisfaction, skills development, and ultimately, higher retention rates.